2013
DOI: 10.1139/cjm-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression ofHelicobacter pyloriVacA N-terminal fragment induces proinflammatory cytokine expression and apoptosis in human monocytic cell line through activation of NF-κB

Abstract: Vacuolating cytotoxin (VacA) is an important virulence factor in the pathogenesis of Helicobacter pylori-related diseases. The aim of this study was to investigate the function of the amino-terminal 476 residue fragment (p52) of VacA and the possible molecular mechanisms responsible for its induction of proinflammatory cytokines secretion and apoptosis. Human acute monocytic leukemia cell line THP-1 was used as an in vitro model to study proinflammatory cytokines secretion and apoptosis induced by transfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…VacA plays several roles in cellular pathogenicity (Table 1), and it is considered a multifunctional toxin eliciting multiple effects on host cells like vacuolization and cell necrosis [56,57]. Numerous studies have also shown cell apoptosis induction by VagA through the mitochondrial pathway in gastric epithelial cells [58,59,60]. An additional apoptotic potential was elaborated in a study, which provided novel evidence that VacA triggers the endoplasmic reticulum stress response to activate autophagy and increased cellular death of AGS cells [61].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…VacA plays several roles in cellular pathogenicity (Table 1), and it is considered a multifunctional toxin eliciting multiple effects on host cells like vacuolization and cell necrosis [56,57]. Numerous studies have also shown cell apoptosis induction by VagA through the mitochondrial pathway in gastric epithelial cells [58,59,60]. An additional apoptotic potential was elaborated in a study, which provided novel evidence that VacA triggers the endoplasmic reticulum stress response to activate autophagy and increased cellular death of AGS cells [61].…”
Section: Virulence Factors Associated With Gastric Epithelial Cellmentioning
confidence: 99%
“…Since various cell types are able to activate the NF-κB pathway in response to TNF-α via TNFR1, the activation of NF-κB not only serves a crucial function in inhibiting apoptosis by inducing the upregulation of key antiapoptotic proteins, such as Bcl-2, Bcl-extra large and X-linked inhibitor of apoptosis protein (33,34), but may also perform a proapoptotic function (35,36). The results of the present study demonstrate that LRP1-knockdown chondrocytes exhibit increased susceptibility to cell death in response to TNF-α, as indicated by the TUNEL assay and the nucleic morphological alterations of apoptotic chondrocytes stained with 4' ,6-diamidino-2-phenylindole (Fig.…”
mentioning
confidence: 99%
“…As H. pylori can trigger STAT3, c-Jun, NF-jB and ERK activation in gastric carcinogenesis, [6][7][8][9]13,14 we next explored whether these proteins may regulate TMEFF2 expression. Gastric cells were treated with H. pylori after knockdown of STAT3, c-Jun, NF-jB and ERK, respectively.…”
Section: Tmeff2 Was Deregulated In H Pylori-related Gastric Carcinogmentioning
confidence: 99%
“…Helicobacter pylori ( H. pylori ) is considered as the strongest risk factor among the host genetic and environmental factors influencing the occurrence and progression of GCs . H. pylori triggers multiple pathways (JAK/STAT3, NF‐κB, PI3K/Akt, Wnt/β‐catenin and Ras/Erk) in gastric epithelial cells and induces complex alterations of these host signaling pathways . Dana et al demonstrated H. pylori induced STAT3 activation both in vitro and in vivo .…”
mentioning
confidence: 99%
See 1 more Smart Citation